1998
DOI: 10.1001/jama.279.19.1537
|View full text |Cite
|
Sign up to set email alerts
|

Role of Rifampin for Treatment of Orthopedic Implant–Related Staphylococcal Infections <SUBTITLE>A Randomized Controlled Trial</SUBTITLE>

Abstract: for the Foreign-Body Infection (FBI) Study GroupContext.-Rifampin-containing regimens are able to cure staphylococcal implant-related infections based on in vitro and in vivo observations. However, this evidence has not been proven by a controlled clinical trial.Objective.-To evaluate the clinical efficacy of a rifampin combination in staphylococcal infections associated with stable orthopedic devices.Design.-A randomized, placebo-controlled, double-blind trial conducted from 1992 through 1997.Setting.-Two inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
642
4
41

Year Published

1998
1998
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 994 publications
(704 citation statements)
references
References 33 publications
17
642
4
41
Order By: Relevance
“…Decision on a suitable antibiotic therapy was made in an interdisciplinary case discussion at the beginning of therapy, according to the detected pathogen and its susceptibility pattern as well as to published recommendations [6,8,25,27].…”
Section: Methodsmentioning
confidence: 99%
“…Decision on a suitable antibiotic therapy was made in an interdisciplinary case discussion at the beginning of therapy, according to the detected pathogen and its susceptibility pattern as well as to published recommendations [6,8,25,27].…”
Section: Methodsmentioning
confidence: 99%
“…The duration of symptoms is important, since several studies have shown a high success rate (82-100%) with debridement and retention, if the duration is 3 weeks (Burger et al 1991, Widmer et al 1992, Zimmerli et al 1998, Tattevin et al 1999, Meehan et al 2003, Barberan 2006, Laffer et al 2006. The time to diagnosis of infection, described by Choong et al (2007) ranged from 5 to 105 days.…”
mentioning
confidence: 99%
“…Curative treatment of infections in totally replaced hips without removal of the implant is occasionally reported in patients with a short history of infection and stable implants (Crockarell et al 1998, Zimmerli et al 1998. We had an unusual case of a long-standing infection adjacent to an uncemented hip prosthesis cured by repeated intra-articular injections of teicoplanin in combination with oral antibiotics.…”
Section: Discussionmentioning
confidence: 97%